Knowledge, attitude and practice of health education students for stem cell donation and transplantation - Gumus Sekerci, Yasemin; Kir Bicer, Emine (Annals of Medical Research, 2021)
Aim: The aim of this study is to determine the knowledge, attitudes and practices of stem cell donation and transplantation of health education students and to investigate their relationship with sociodemographic factors.Material and Methods: This descriptive and cross-sectional study was conducted with 419 students studying in the departments of Nursing, Physical Therapy and Rehabilitation, Emergency and Disaster Management in the fall semester of a university in 2019-2020 academic year. Data were collected by using the descriptive information form, Stem Cell Information Form, and Stem Cell Attitude Form. Data were analyzed using frequency, percentage, mean, standard deviation, independent test, One-way ANOVA, Tukey HSD test and correlation analysis.Results: The mean age of the participants was 20.68 ± 2.18 year and 68.3% were female. The majority of the participants had clinical experience. Although 52.5% of the participants wanted to be stem cell donors, only 3.6% donated stem cells. The participants' knowledge scores for stem cell donation and transplantation were 22.31 ± 9.38 and attitude scores were 38.88 ± 4.58. Several socio-demographic factors affecting the stem cell knowledge and attitudes of the students were determined. In addition, a statistically weakly significant correlation was found between the participants' stem cell knowledge and stem cell attitudes (r = .237, p .001).Conclusion: In the study, it was concluded that the stem cell donation rate of the students receiving health education was low, they had moderate knowledge about stem cell donation and transplantation and they showed positive attitude.
Keywords: Health education; stem cell; transplantation